Examining the connection between nature connectedness and dark personality. (December 2020) - Fido, D.; Rees, A.; Clarke, P.; Petronzi, D.; Richardson, M.
Abstract: The psychological construct of nature connectedness - the depth of an individual's relationship with the natural world - has not only been associated with benefits for mental well-being but has also shown relationships with personality traits relevant to the dark personality literature. These include agreeableness, cognitive and affective empathy, and callous and uncaring traits. Across two independently-sampled studies we delineate relationships between explicit and implicit indices of nature connectedness and dark personality. In Study 1 ( N = 304), psychopathy (and Machiavellianism) was associated with self-reported, but not implicitly-measured, nature connectedness. Moreover, individuals scoring high on dark personality exhibited a preference for inner-city, relative to suburban or rural living. In Study 2 ( N = 209), we replicated the findings of Study 1 in relation to explicit measures of nature connectedness but did not find further relationships between dark personality and the population densities of where participants had previously lived. Limitations of implicit and pseudo indices of nature connectedness are outlined, and the results are discussed in relation to future research and the potential role of nature connectedness interventions in forensic populations. Data, syntax, and the manuscript pre-print are available here: [https://osf.io/3mg5d/?view_only=b5c7749d4a7945c5a161f0915a2d0259 ]. Highlights: Psychopathy is inversely associated with nature connectedness. High scoring on psychopathy was associated with a preference for inner-city living, but did not match residential history. The nature-based IAT may not be a valid measure of implicit nature connectedness.